Insurance Business in Economic Development in Pematangsiantar City - Parlin Dony Sipayung (Randwick International of Social Science Journal, 2022)
The development of economic potential such as the insurance business needs to be carried out efficiently through careful planning so that the insurance economic resources owned can be used continuously and passed on to generations in Pematangsiantar city. How positive expectations from the insurance business as an insurance business in Pematangsiantar City form an agreement that binds the insurance agreement What obstacles are faced by the cause of the insurance business in Pematangsiantar in economic development. The positive expectation from the insurance business can be transformed into an insurance business, which means entering premiums which then become funds. Funds stored for a period of time in an insurance company can be used by the company to finance a business that is profitable for them in addition to helping the community increase their businesses by providing capital or credit for the short and long term. All of these efforts have clearly helped economic development in the Republic of Indonesia. The form of the insurance agreement is a standard agreement or "standard contract" where the agreement whose contents are standardized and stated in the form of a form. The obstacles in the practice of insurance business in Pematangsiantar City are when the customer pays less attention to and understands the conditions specified in the standard agreement before the agreement held.